A short-term, randomized, controlled, feasibility study of the effects of different vegetables on the gut microbiota and microRNA expression in infants - Ferro, Lynn E.; Bittinger, Kyle; Trudo, Sabrina P.; Beane, Kaleigh E.; Polson, Shawn W.; Kim, Jae Kyeom; Trabulsi, Jillian C. (Frontiers in Microbiomes, 2024)
The complementary diet influences gastrointestinal (gut) microbiota composition and in turn, host health and potentially microRNA (miRNA) expression. This study aimed to assess the feasibility of altering gut microbial communities with short term food introduction and to determine the effects of different vegetables on the infant gut microbiota and miRNA expression. Eleven infants were randomized to one of the following intervention arms: control, broccoli, or carrot. The control group maintained the milk diet only, while the other groups consumed either a broccoli puree or a carrot puree on days 1-3 along with their milk diet (human milk or infant formula). Genomic DNA and total RNA were extracted from fecal samples to measure microbiota composition and miRNA expression. The short-term feeding of both broccoli and carrots resulted in changes in microbiota and miRNA expression. Compared to control, a trend towards a decrease in Shannon index was observed in the carrot group on days 2 and 4. Carrot and broccoli groups differed by weighted UniFrac. Streptococcus was increased at day 4 in carrot compared to control. Expression of two miRNAs (miR-217, -590-5p) decreased in both broccoli and carrot groups compared to control, whereas an increase in eight and two different miRNAs were observed in carrot and broccoli groups, respectively. Vegetable interventions differentially impacted gut microbiota and miRNA expression, which may be a mechanism by which total vegetable intake and variety are associated with reduced disease risk.